Operation and Management of Seoul Metropolitan City Community Treatment Center for Mild Condition COVID-19 Patients - Lee, Sun Young (J Korean Med Sci, 2020)
BACKGROUND: In response to the disaster of coronavirus disease 2019 (COVID-19) pandemic, Seoul Metropolitan Government (SMG) established a patient facility for mild condition patients other than hospital. This study was conducted to investigate the operation and necessary resources of a community treatment center (CTC) operated in Seoul, a metropolitan city with a population of 10 million. METHODS: To respond COVID-19 epidemic, the SMG designated 5 municipal hospitals as dedicated COVID-19 hospitals and implemented one CTC cooperated with the Boramae Municipal Hospital for COVID-19 patients in Seoul. As a retrospective cross-sectional observational study, retrospective medical records review was conducted for patients admitted to the Seoul CTC. The admission and discharge route of CTC patients were investigated. The patient characteristics were compared according to route of discharge whether the patient was discharged to home or transferred to hospital. To report the operation of CTC, the daily mean number of tests (reverse transcription polymerase chain reaction and chest X-ray) and consultations by medical staffs were calculated per week. The list of frequent used medications and who used medication most frequently were investigated. RESULTS: Until May 27 when the Seoul CTC was closed, 26.5% (n = 213) of total 803 COVID-19 patients in Seoul were admitted to the CTC. It was 35.7% (n = 213) of 597 newly diagnosed patients in Seoul during the 11 weeks of operation. The median length of stay was 21 days (interquartile range, 12–29 days). A total of 191 patients (89.7%) were discharged to home after virologic remission and 22 (10.3%) were transferred to hospital for further treatment. Fifty percent of transferred patients were within a week since CTC admission. Daily 2.5–3.6 consultations by doctors or nurses and 0.4–0.9 tests were provided to one patient. The most frequently prescribed medication was symptomatic medication for COVID-19 (cough/sputum and rhinorrhea). The next ranking was psychiatric medication for sleep problem and depression/anxiety, which was prescribed more than digestive drug. CONCLUSION: In the time of an infectious disease disaster, a metropolitan city can operate a temporary patient facility such as CTC to make a surge capacity and appropriately allocate scarce medical resource.